2017
DOI: 10.3389/fpls.2017.00849
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Soil Bacterial Communities in a Chronosequence of Rubber Tree (Hevea brasiliensis) Plantations

Abstract: Regarding rubber tree plantations, researchers lack a basic understanding of soil microbial communities; specifically, little is known about whether or not soil microbial variation is correlated with succession in these plantations. In this paper, we used high-throughput sequencing of the 16S rRNA gene to investigate the diversity and composition of the soil bacterial communities in a chronosequence of rubber tree plantations that were 5, 10, 13, 18, 25, and 30 years old. We determined that: (1) Soil bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 60 publications
6
51
0
Order By: Relevance
“…A survey conducted at the onset of this study revealed that they only used inorganic fertilizers including urea and NPK as inputs in the early stages of the plantations to help trees grow smoothly. The chronosequence that is a set of rubber tree plantations in the landscape that share similar attributes but with different ages, was found to be most relevant approach in line with the objective of this study as the initial date of the disturbance and subsequent history of the sites were known (Walker et al, 2010;Zhou et al, 2017). The general assumption supporting chronosequence-based study uses natural forests as baseline ecosystems from which all man-made systems were at first derived.…”
Section: Sampling Designmentioning
confidence: 75%
“…A survey conducted at the onset of this study revealed that they only used inorganic fertilizers including urea and NPK as inputs in the early stages of the plantations to help trees grow smoothly. The chronosequence that is a set of rubber tree plantations in the landscape that share similar attributes but with different ages, was found to be most relevant approach in line with the objective of this study as the initial date of the disturbance and subsequent history of the sites were known (Walker et al, 2010;Zhou et al, 2017). The general assumption supporting chronosequence-based study uses natural forests as baseline ecosystems from which all man-made systems were at first derived.…”
Section: Sampling Designmentioning
confidence: 75%
“…Our results showed no significant difference in the soil nutrients (N, P, and K).Only soil pH significantly decreased in the 30-year-old tea plantation when compared with the bulk soil and the two-year-old tea field, which resulted in lowering the abundance of rhizospheric microbiota, such as Actinobacteria , Cyanobacteria , Chloroflexi , and WD272 [ 35 ], and showed direct association with Nitrospirae , Gemmatimonadetes , and Acidobacteria. On the other hand, Proteobacteria and Bacteroidetes were the most dominant bacterial group present in the 30-year-old tea plantation [ 43 , 44 ], which may be because these bacterial taxa prefer to live in a root vicinity with nutrient deficiency, high soil moisture (MOS), and lower pH. Previous studies on bacterial communities have clearly shown that nutrient deficiency did not significantly impact the soil microbiota, however soil pH was proven to be the most influential factor in shaping the soil microbiota [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quantity and purity of DNA were checked by NanoDrop2000 spectrophotometer (Thermo Fisher Scientific, Waltham, Massachusetts, USA). The universal 16S rRNA gene primers 515F (5 -GTGCCAGCMGCCGCGG-3 ) and 970R (5 -CCGTCAATTCMTTTRAGTTT-3 ) were used for the amplification and subsequent high-throughput sequencing of the PCR products [33]. ‱ C until halted by user.…”
Section: Dna Extraction Pcr Amplification and High Throughput Sequementioning
confidence: 99%